COVID-19 and Skin Manifestations: An Overview of Case Reports/Case Series and Meta-Analysis of Prevalence Studies - Sameni, Fatemeh; Hajikhani, Bahareh; Yaslianifard, Somayeh; Goudarzi, Mehdi; Owlia, Parviz; Nasiri, Mohammad Javad; Shokouhi, Shervin; Bakhtiyari, Mahmood; Dadashi, Masoud (Frontiers in Medicine, 2020)
Background and Aim: Since the onset of the 2019-nCoV disease (COVID-19) many skin manifestations have been reported in COVID-19 patients. This study aims to provide a systematic review and meta-analysis of various skin manifestations among patients with COVID-19 through case reports/case series and prevalence studies. Methods: A systematic literature search was conducted via reviewing original research articles published in Medline, Web of Science, and Embase databases in 2020. Statistical analysis was performed with STATA software, version 14.0 (Stata Corporation, College Station, Texas, USA) to report the global prevalence of skin manifestations among patients with COVID-19. Results: Forty-three studies (25 articles were case reports/case series and 8 articles were prevalence studies) were included in our study. A meta-analysis of prevalence studies showed that skin manifestations among patients with COVID-19 were reported in 5 countries (China, Thailand, France, and Italy), with an overall prevalence of 1.0 % [(95% CI) 0.1-1.9] among 2621 patients. Evaluation of the results of the case reports/case series revealed that out of 54 patients with COVID-19, 48 patients (88.8%) showed skin manifestations. Erythematous lesion (35.1%), Rash (24.0%) and Urticaria (14.8%) were the most common skin presentation reported in studied patients. Conclusion: Infection with 2019-nCoV may lead to skin manifestations with various clinical symptom. These clinical features combined with a clinical COVID-19 symptom may aid in the timely diagnosis of patients with COVID-19.